Production of monoclonal antibody against eyestalk neuropeptide hormones in the black tiger prawn neuropeptide hormones in the black tiger prawn Penaeus monodon - Nanthika Panchan (Chulalongkorn University, 2007)
Thesis (Ph.D.)--Chulalongkorn University, 2004